Do radiation oncologists and urologists endorse decision aids for active surveillance of low‐risk prostate cancer: Results from a national survey. (27th October 2020) - Puneet, Kang; Tilburt, Jon C.; Volk, Robert J.; Bennett, Charles L.; Qureshi, Zaina; Gershman, Boris; Sedlacek, Hillary M.; Kim, Simon P.
Abstract: Objective: The degree decision aids (DAs) can promote active surveillance (AS) for prostate cancer (PCa) remains poorly understood. Herein, we surveyed radiation oncologists (RO) and urologists (URO) about their attitudes towards DAs in counselling patients about AS for low‐risk PCa. Methods: We conducted a national survey of RO ( n = 915) and URO ( n = 940) to assess their attitudes about DAs for AS for patients with low‐risk PCa. Respondents were queried about their attitudes towards DAs and proportion of PCa patients managed with AS. Multivariable logistic regression models were used to examine physician characteristics related to attitudes about DAs. Results: The overall response rate was 37.3% ( n = 691). Most respondents strongly agreed or agreed that DAs helped patients with low‐risk PCa make informed decisions (93.9%) and also increased patient support for AS (86.6%). Having a high volume of their low‐risk PCa patients on AS (>15%) was associated with endorsing the statement that use of DAs increased the likelihood of recommending AS (OR: 1.83; 95% CI: 1.00–4.61; p = .05) and being a URO versus a RO (OR: 3.37; 95% CI: 2.46–5.79; p < .001). Conclusions: Most specialists view DAs as effective tools to facilitate more informed treatment decisions and facilitate greater use of AS in appropriately selected patients.